ANALYSIS AND DESIGN ON VARYING THE OFFSETS IN SUPERIMPOSED MECHANICALLY STABILIZED EARTH WALLS - Vuttichai Chatpattananan (International Journal of Geomate, 2022)
Superimposed MSE walls or multi-tier MSE walls are frequently used due to their eye-pleasing, economical, and safety requirements compared with single-tall MSE walls. Designing an MSE wall requires checking the failure modes in its external stability, internal stability, and global stability. Calculating the external stability and global stability for superimposed walls is well explained. Internal stability, however, is more complicated in calculating the additional vertical stress from the upper wall as an equivalent surcharge on the lower wall with its magnitude determined by the offset distance. By varying offset distances, the additional vertical stress can be categorized into three cases. Case 1 is the maximum additional vertical from the upper wall load when the offset distance is less than HLtan(45-r/2). The additional vertical stress is zero in case 3 where the offset distance is greater than H L tan(90- r ). In case 2, the additional vertical stress is a hyperbola function that can be calculated easily using the proposed equation i = [(H L -z 1 )/(z 2 -z 1 )](H U +q) in Eq. (
Keywords: Geotechnical Engineering and Soil Stabilization